The effect of application of standard audit hour on audit quality under external audit law – Evidence from Korea - Kyong-Yong Kim; Kyunbeom Jeong (Cogent Business & Management, 2022)
This paper investigates the effect of the application of standard audit hour on audit quality under the external audit law in Korea. As a result of empirical analysis, first, it is confirmed that the absolute value of the discretionary accrual decreased due to the application of the standard audit hour under the external audit law, so the audit quality improved. Second, the degree to which audit quality improves due to the application of standard audit hour is greater when the rate of increase in audit hour is high. Third, the degree to which audit quality improves according to the rate of increase in audit hour due to the application of standard audit hour is greater when the proportion of quarterly or semi-annual review time is high. Fourth, the degree to which audit quality improves according to the rate of increase in audit hour due to the application of standard audit hour does not appear larger when the proportion of audit hour of senior auditors is high. This study is the first to comprehensively verify the effect of the standard audit hour under the external audit law in Korea, and the results of this study are useful for related institutions to operate the standard audit hour and are expected to have implications in the future.
Keywords: 650; audit quality; Audit hour; Audit hour by senior auditors; quarterly review hour (ratio); standard audit hour